Accompagnement de l’autonomisation dans des dispositifs d’apprentissage des langues médiatisés : des leviers récurrents - Elke Nissen (Recherches en didactique des langues et des cultures)
In the recent context where many courses worldwide have had to go online as a matter of urgency, the question of learners’ autonomisation within e-learning settings has taken on new importance. This paper draws a parallel with other types of language learning settings that take place partly or entirely at a distance. It focuses on how they support learner autonomisation and, drawing on the literature in the field, identifies the levers for helping learners to take responsibility and show agency in their learning process within these settings. The major levers identified in the different types of settings can be addressed at the socio-affective, design and technical levels.